Advances in medical applications: the quest of green nanomaterials - Azmi, Nor Azrini Nadiha; Elgharbawy, Amal A.M. (Springer Cham, 2022)
Nanotechnology emphasizes the use of specialized structures or materials at the nanoscale, which is defined as a size of 100 nm or less. Since the last few decades, nanotechnology and nanomaterials have developed significantly in many fields. Materials engineered to such a small scale are fascinating because of their microscopic size and increased surface-to-volume ratio. Recently, the future of nanotechnology seemed to be even brighter when green chemistry came into the picture. In green nanotechnology, nanomaterials are usually synthesized by biosynthesis, regarded as eco-friendly, efficient, and easily scaled up. Due to these factors, green nanomaterials have been considerably explored in the last several years, especially in the biomedical field. The major applications for green nanomaterials are divided into three sections: drug delivery, therapy, and diagnosis. Nanomaterials focus on bioimaging and biosensors for diagnosis, while nanomaterials are mainly used in cancer treatment and antibacterial agents for therapy. Because most biological processes are nanoscale, nanomaterials work perfectly with biomedical equipment. Until now, several green nanomaterials have been successfully utilized in therapeutics drug delivery and bioimaging. Nevertheless, while green nanomaterials are rising in popularity in the biomedical field, some issues must be addressed, especially toxicity. This review presents the potential applications of green nanomaterials in biomedical applications thoroughly.